Automated fire alarm system / Mohamad Alif Mat Abu and Ahmad Afifi Ahmad Afandi - Mat Abu, Mohamad Alif; Ahmad Afandi, Ahmad Afifi (2015)
Fire alarm system plays important role to maintain and monitoring the safe of all kind environment and situations. This system is important for early detection and promptly extinguishing fire. Nowadays, we always heard about the fire conflagration often. The system is made to warn human and make people more careful at any time and places. So this system must located at any places because it functions to detect fire rapidly and also costless. Fire alarm system divided into two main system that is detection system and monitoring system. The detection system operates as the fire detector. This detection system has two detection component which are smoke detector and heat detector. This project discuss the design and implementation of fire alarm system using microcontroller which operates the entire system. The monitoring system is developed such way and will display the output. The project start operates when the detection system detect fire when existing of heat at particular level. Finally when the sensor from each level triggered, the buzzer will produce sound and LED will light up.